Together at the table : sustainability and sustenance in the American agrifood system - Allen, Patricia, 1954- (Rural studies series (University Park, Pa.), 2004)
Everywhere you look, people are more aware of what they eat and where their food comes from. In a cafeteria in Los Angeles, children make their lunchtime food choices at fresh-fruit and salad bars stocked with local foods. In a community garden in New York, low-income residents are producing organically grown fruits and vegetables for their own use and to sell at market. In Madison, Wisconsin, shoppers select their food from a bounty of choices at a vibrant farmers' market. Together at the Table is about people throughout the United States who are building successful alternatives to the contemporary agrifood system and their prospects for the future. At the heart of these efforts are the movements for sustainable agriculture and community food security. Both movements seek to reconstruct the agrifood system-the food production chain, from the growing of crops to food production and distribution-to become more ecologically sound, economically viable, and socially just. Allen describes the ways in which people working in these movements view the world and how they see their place in challenging and reshaping the agrifood system. She also shows how ideas and practices of sustainable agriculture and community food security have already woven their way into the dominant agrifood institutions. Allen explores the possibilities this process may hold for improving social and environmental justice in the American agrifood system. Together at the Table is an important reminder that much work still remains to be done. Now that the ideas and priorities of alternative food movements have taken hold, it is time for the next-even more challenging-step. Alternative agrifood movements must acknowledge and address the deeper structural and cultural patterns that constrain the long-term resolution of social and environmental problems in the agrifood system.